Synthesis of Benzofuroquinolines via Phosphine-Free Direct Arylation of 4-Phenoxyquinolines in Air - Shanahan, R.; Hickey, A.; Reen, F.; O'Gara, Fergal; McGlacken, G. (Wiley-VCH Verlag GMBH, 2018)
© 2018 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim A palladium-catalysed, phosphine-free, direct arylation of 4-phenoxyquinolines, in air is described. Using an intramolecular approach, the ring-closed products are formed in yields of up to 95 %. This approach allows access to a range of benzofuroquinolines. An array of functional groups on both the quinoline and phenoxy rings are tolerated.